Infection Markers as Prediction of Neonatal Sepsis - Cindy Clarissa Sirait; Bugis Mardina Lubis; Ika Citra Dewi Tanjung; Hendri Wijaya; Arlinda Sari Wahyuni; Ayodhia Pitaloka Pasaribu (Indonesian Journal of Global Health Research, 2025)
Neonatal sepsis is one of the most common causes of neonatal death in the first month of life. Neonatal sepsis often shows atypical clinical features include temperature instability, lethargy, skin changes, feeding problems, and many others. Isolation of bacteria from the culture is the gold standard for diagnosing sepsis, but this approach is frequently time-consuming and even in cases of negative blood cultures, sepsis cannot be conclusively ruled out, posing a major challenge in its diagnosis and management. Early diagnosis and timely intervention are essential to improve the prognosis of neonatal sepsis. Aim: The aim of this study is to discuss how infection markers can aid in the early identification of neonatal sepsis and what are the best infection markers to predict neonatal sepsis mortality. Method: This study assessed the diagnostic accuracies of infection marker used in the diagnosis of neonatal sepsis. Included studies were retrieved by searching three major databases (Google Scholar, Pubmed, and Science Direct) using MeSH words and relevant references, and reviewed based on the inclusion/exclusion criteria. The article discusses potential advancements and future prospects for biomarkers. An excellent marker can guide antibiotic administration and duration if sepsis is confirmed, reducing unnecessary use. The marker should have high sensitivity, specificity, positive predictive value, negative predictive value and accuracy.